Toughening of polyamide 11 with carbon nanotubes for additive manufacturing. Issue 3 (3rd July 2017) - Bai, Jiaming; Yuan, Shangqin; Shen, Fei; Zhang, Baicheng; Chua, Chee Kai; Zhou, Kun; Wei, Jun
ABSTRACT: It has been reported that the addition of nanofillers/nanoparticles into the thermoplastic polymers could enhance the toughness of the polymer matrix. In this work, the mechanical and thermal properties of a multi-walled carbon nanotubes (CNT)/polyamide 11 nanocomposite for additive manufacturing was evaluated. Well-dispersed PA11/CNT nanocomposite powders were processed successfully by laser sintering. Compared to the pristine PA11, the fracture toughness of the PA11/CNT nanocomposite was enhanced by ∼54% by incorporating of only 0.2 wt% CNTs. With differential scanning calorimetry, X-ray diffraction and scanning electron microscope fractography analysis, the nanostructure and the toughening mechanism which lead to the toughness improvement was well identified and understood.